Relationship between nutritional intake and the duration of mechanical ventilation use in critical patients. - Lidya Istiqomah, Yunita; BUKHARI, Agussalim; AS’AD, Suryani; TASLIM, Nurpudji A.; SYAUKI, Yasmin; RASYID, Haerani; ABADI, Tien Muliawati; HUSMIANI; JEFFERY; BUANA, Desi Vera (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: The incidence of malnutrition among critically ill patients undergoing treatment in intensive care unit (ICU) ranges from 30-50%. This malnutrition is primarily attributed to hypercatabolism and hypermetabolism, leading to significant reductions in energy and protein levels. Muscle atrophy, particularly in the diaphragm, exacerbates respiratory muscle fatigue, making breathing difficult and necessitating prolonged mechanical ventilation. Objectives: This study aims to examine the relationship between energy, protein, carbohydrate, and fat intake and the duration of mechanical ventilation in patients receiving collaborative clinical nutrition (first group) versus non-collaborative clinical nutrition (second group) Methods: This retrospective cohort study employed an analytical observational approach and was conducted at the Medical Records section of Wahidin Sudirohusodo Hospital in Makassar. The study included 37 patients who had been on mechanical ventilation for ≥ 8 days and received enteral and parenteral nutrition. The patients were divided into two groups: one receiving collaborative clinical nutrition and the other receiving only enteral nutrition. Data collection involved 24-hour food recall recording, blood tests for routine parameters, and assessment of the duration of mechanical ventilation. Results: The study found significant differences in nutritional intake between the collaborative clinical nutrition (first group) and the non-collaborative clinical nutrition (second group). The collaborative group had higher mean energy (first group 1199.70 vs. second group 848.73), protein (first group 22.38 vs. second group 17.29), and fat (first group 22.62 vs. second group 15.31) intake, while carbohydrate intake was lower in the first group (55.30 vs. second group 63.86). These differences were statistically significant with a p-value < 0.05. This study also found a correlation between nutritional intake and duration of mechanical ventilation use. There was a negative correlation between energy, protein and fat intake while carbohydrate intake had a positive correlation. Conclusions: The study concludes that the collaborative clinical nutrition (first group) had higher nutritional intake compared to the non-collaborative (second group).